2000
DOI: 10.1152/jn.2000.84.4.1982
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Mechanisms Underlying Activity Patterns in the Monkey Thalamus During Visual Behavior

Abstract: We show for the first time with in vitro recording that burst firing in thalamic relay cells of the monkey is evoked by activation of voltage-dependent, low threshold Ca(2+) spikes (LTSs), as has been described in other mammals. Due to variations in LTS amplitude, the number of action potentials evoked by an LTS could vary between 1 and 8. These data confirm the presence of two modes of firing in the monkey for thalamic relay cells, tonic and burst, the latter related to the activation of LTSs. With these deta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
20
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 24 publications
5
20
0
Order By: Relevance
“…11 and 38; for review see ref., 39) and in vivo (1,40). These results corroborate other studies that have shown bursting activity during wakefulness in cats (13,14), guinea pigs (15), rabbits (16), and monkeys (17,18). Thus, it is clear that bursting can occur during wakefulness and, indeed, can be observed during periods of sensory processing (12)(13)(14).…”
Section: The Burst Firing Mode Is Not Limited To Sleep and Pathologicsupporting
confidence: 87%
See 1 more Smart Citation
“…11 and 38; for review see ref., 39) and in vivo (1,40). These results corroborate other studies that have shown bursting activity during wakefulness in cats (13,14), guinea pigs (15), rabbits (16), and monkeys (17,18). Thus, it is clear that bursting can occur during wakefulness and, indeed, can be observed during periods of sensory processing (12)(13)(14).…”
Section: The Burst Firing Mode Is Not Limited To Sleep and Pathologicsupporting
confidence: 87%
“…11 for review), such as during slow-wave sleep, barbiturate anesthesia, and pathological conditions such as seizure activity. However, it has recently been demonstrated that thalamic bursting can occur during awake states as well, in multiple species (12)(13)(14)(15)(16)(17)(18), and that sensory information can be conveyed to the cortex during the burst activity (16).…”
mentioning
confidence: 99%
“…Any action potential with a preceding interval of Ն100 ms, followed by action potentials within 4 ms of each other, were all counted as burst mode. We had shown earlier that the basic cellular mechanisms that apply to burst firing for thalamic neurons are also present in the monkey (28). All other action potentials that did not fit into this category were counted as tonic mode.…”
Section: Resultsmentioning
confidence: 99%
“…These authors showed that Ͼ98% of "bursts" identified using these criteria were attributable to LTS activity. Given that LTS activity and burst firing appear rather conserved across different mammalian species (Jahnsen and Llinas, 1984;McCormick and Feeser, 1990;Zhan et al, 1999;Ramcharan et al, 2000), including mice (Kim et al, 2001), the same criteria were used to identify burst firing in the responses of mouse dLGN neurons here. Specifically, the first action potential in a burst had a preceding silent period of Ն100 msec and a following interspike interval (ISI) of Յ4 msec.…”
Section: Methodsmentioning
confidence: 99%